64 Effect modification of familial longevity on the association between kidney dysfunction, cardiovascular disease, and mortality - Laith Alzyood; Tina Goa; Einstein Sanish Sathyan; Einstein Sandra Aleksic; Einstein Sofiya Milman; Einstein Michal Melamed; Wei Chen Einstein (Journal of Clinical and Translational Science)
Objectives/Goals: Objective: To examine whether familial longevity modifies the relationship between chronic kidney disease (CKD) and cardiovascular disease (CVD) in older adults. Goals include assessing the impact of familial longevity on 1) CVD prevalence, 2) CVD incidence, and 3) mortality among individuals with CKD. Methods/Study Population: An observational, longitudinal study. We examined 1,236 Ashkenazi Jewish adults (ages 65–94) from the LonGenity cohort. Estimated glomerular filtration rate (eGFR) was the independent variable, calculated using the CKD-EPI equation 2021. CVD prevalence, incidence, and mortality were our outcomes. CVD was defined as a composite of MI, PCI, CABG, or stroke. Exceptional longevity was defined as living past 95 years, grouping participants into OPEL (offspring of parents with exceptional longevity, n = 576) and OPUS (offspring of parents with usual survival, n = 604). Stratified logistic regression and Cox proportional hazards models assessed eGFR’s association with CVD, testing effect modification through eGFR × OPEL interaction terms. Median follow-up was 5.5 years. Results/Anticipated Results: A significant association was observed between eGFR and CVD prevalence in OPUS, but not in OPEL. No significant link was found between eGFR and CVD incidence or mortality in either group. Familial longevity did not modify the association between eGFR and CVD prevalence, nor the composite of CVD incidence and mortality, as the interaction term was nonsignificant. The LonGenity cohort’s health status may have influenced these results due to selection and survivor biases, limiting generalizability. Further research is needed to clarify familial longevity’s role in kidney function and cardiovascular outcomes. Discussion/Significance of Impact: Our findings suggest that kidney function, as measured by eGFR, may be associated differently with cardiovascular risk in those with and without familial longevity. The study highlights potential limits of familial longevity in modifying CVD risk associated with CKD, underscoring the need for tailored CVD prevention strategies.